Assessment of public charging infrastructure push and pull rollout strategies: The case of the Netherlands. (October 2018) - Helmus, J.R.; Spoelstra, J.C.; Refa, N.; Lees, M.; van den Hoed, R.
Abstract: Over recent years, numbers of electric vehicles (EVs) have shown a strong growth and sales are projected to continue to grow. For facilitating charging possibilities for EVs typically two rollout strategies have been applied; demand-driven and strategic rollout. This study focuses on determining the differences in performance metrics of the two rollout strategies by first defining key performance metrics. Thereafter, the root causes of performance differences between the two rollout strategies are investigated. This study analyzes charging data of 1, 007, 137 transactions on 1742 different CPs by use of 53, 850 unique charging cards. This research concludes that demand-driven CPs outperform strategic CPs on weekly energy transfer and connection duration, while strategic CPs outperform their demand-driven counterparts on charging time ratio. Regarding users facilitated, there is a significant change in performance after massive EV-uptake. The root cause analysis shows effects of EV uptake and user type composition on the differences in performance metrics. This research concludes with implications for policy makers regarding an optimal portfolio of rollout strategies. Highlights: This research analyzes more than 1 million charging sessions on public charging infrastructure. KPIs for strategic and demand-driven rollout strategies are defined and compared. Root cause analysis shows effects of EV uptake and user types on the differences in KPIs. Demand driven charging points perform better in immature markets. Strategic charging points perform better on facilitation of EV users.